2008
DOI: 10.1063/1.2844885
|View full text |Cite
|
Sign up to set email alerts
|

Plasma power measurement and hysteresis in the E–H transition of a rf inductively coupled plasma system

Abstract: An experimental investigation of the argon plasma behavior near the E–H transition in an inductively coupled Gaseous Electronics Conference reference cell is reported. Electron density and temperature, ion density, argon metastable density, and optical emission measurements have been made as function of input power and gas pressure. When plotted versus plasma power, applied power corrected for coil and hardware losses, no hysteresis is observed in the measured plasma parameter dependence at the E–H mode transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 10 publications
4
40
1
Order By: Relevance
“…Experimentally, decrease in plasma potential during E/H transition was confirmed by Seo et al 3 Singh et al 4 and Chung et al 5 studied the behaviour and measurement of electron energy distribution function in E mode. The effect of impedance matching network in ionised low pressure ICPs was reported by Ding et al 6 and Daltrini et al 7 Low RF frequency measurements were reported by El-Fayoumi et al 8 and Ostrikov et al 9 and at pulsed plasma by Edamur et al 10 Some theoretical works were also carried out to study E/H mode transition. The critical current for the operation of stable H mode was calculated by Kortshagen et al 11 and skin depth by Lee et al 12 Turner et al 13 and Cunge et al 14 considered the E-H transition mechanism and hysteresis based on the balance equation and the nonlinear effects most notably between power absorptions and power dissipations.…”
mentioning
confidence: 91%
“…Experimentally, decrease in plasma potential during E/H transition was confirmed by Seo et al 3 Singh et al 4 and Chung et al 5 studied the behaviour and measurement of electron energy distribution function in E mode. The effect of impedance matching network in ionised low pressure ICPs was reported by Ding et al 6 and Daltrini et al 7 Low RF frequency measurements were reported by El-Fayoumi et al 8 and Ostrikov et al 9 and at pulsed plasma by Edamur et al 10 Some theoretical works were also carried out to study E/H mode transition. The critical current for the operation of stable H mode was calculated by Kortshagen et al 11 and skin depth by Lee et al 12 Turner et al 13 and Cunge et al 14 considered the E-H transition mechanism and hysteresis based on the balance equation and the nonlinear effects most notably between power absorptions and power dissipations.…”
mentioning
confidence: 91%
“…While the E-H transition is generally reported [4,5,6] as an average increase of the electron density and light emission, our results indicate that its detailed description must take into account the local properties of the plasma as these vary significantly in the chamber volume as a function of time and space.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies [4,5,6] have shown that a sharp transition occurs between these two modes (E-H) if a su ciently high current is driven through the coil. During the transition a sudden jump of the electron density and light emission is observed, accompanied by a modification of the Electron Energy Distribution Function (EEDF) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [9] and Chung et al [10] studied the behaviour and measurement of electron energy distribution function in E mode. The effect of impedance matching network in ionised low pressure ICPs was reported by Ding et al [11] and Daltrini et al [12]. Low RF frequency measurements were reported by El-Fayoumi et al [13] and Ostrikov et al [14] and at pulsed plasma by Edamur et al [15].…”
Section: Introductionmentioning
confidence: 86%